Usher syndrome: clinical signifcance - Fandiño Cardenas, Marcela (2023)
To describe the importance of Usher syndrome and its clinical implications in different patients with auditory and visual pathology, prioritizing its diagnosis, approach and treatment. A literature search was performed in PubMed, SciELO, ScienceDirect databases, prioritizing the updated literature of meta-analysis, observational studies, review articles and systematic reviews, in English or Spanish, published in the last 5 years, in which the relationship between Usher syndrome and visual and auditory alterations was evaluated, with the aim of describing its importance, diagnosis and treatment. Different studies evidence the direct relationship between Usher syndrome and visual and hearing loss, associating it to multiple genetic malformations. Treatment is focused on rehabilitation therapy that allows the individual to adapt to the environment and reduce other associated comorbidities. Usher syndrome is an important cause of visual and auditory dysfunction. Currently, studies continue in search of an effective treatment; however, it is important to make a timely diagnosis by means of suspicion, diagnosis and approach, to allow us to reduce its progression.